AN ANALYSIS AND PERFORMANCE PRACTICE OF "BUSSABA" FOR MARIMBA AND PIANO, COMPOSED BY KITTI KUREMANEE - Yannavut, Wannapha (Mahidol Music Journal, 2024)
An analysis and performance practice of “Bussaba” for marimba and piano, composed by Kitti Kuremanee aim to provide an overall understanding of the piece and offer techniques for practicing and performing effectively on the marimba. The composition “Bussaba” is a fusion of Thai and Western music, incorporating techniques from both traditions. The composer emphasized the importance of understanding, interpreting, and selecting appropriate techniques for marimba performance to enable a successful collaboration with the piano. This fusion allows for easy listening and offers an intriguing blend of Thai and Western musical elements. The composer composed “Bussaba” to promote and preserve Thai music by presenting it in a unique blend with Western music, showcasing Thai melodies, rhythms, and motifs alongside Western harmonies and marimba performance techniques. This artistic endeavor serves to promote Thai culture and heritage successfully.